2011
DOI: 10.1007/s00228-011-1199-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity associated with the recreational use of the ketamine derivative methoxetamine

Abstract: These three analytically confirmed cases demonstrate that acute methoxetamine-related toxicity is associated with both "dissociative" and "sympathomimetic" clinical features. The information from these three cases is useful to clinical pharmacologists, not only in managing individuals with acute methoxetamine toxicity but also in advising the appropriate legislative authorities on the risk of acute harm related to methoxetamine use. Further work is needed to determine whether methoxetamine is more "bladder fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 14 publications
4
73
0
9
Order By: Relevance
“…6,3 Actually, signs and symptoms observed in our patient such as hypertension, tachycardia, confusion, sedation, shifts in perception of reality, agitation, nystagmus, opisthotonus, amnesia, and urinary retention are compatible with the effects induced by MXE, ketamine, and PCP. 7,8,9 Moreover, speech disorders such as pressured speech, verbigerations, and echolalia have been regularly reported by users of PCP and ketamine. 8,9 Hypertension and nystagmus, which were observed in our patient, are hallmarks of PCP intoxication, and both have been reported to occur in about 57% of the cases and to resolve within 4 h of PCP consumption.…”
Section: Discussionmentioning
confidence: 99%
“…6,3 Actually, signs and symptoms observed in our patient such as hypertension, tachycardia, confusion, sedation, shifts in perception of reality, agitation, nystagmus, opisthotonus, amnesia, and urinary retention are compatible with the effects induced by MXE, ketamine, and PCP. 7,8,9 Moreover, speech disorders such as pressured speech, verbigerations, and echolalia have been regularly reported by users of PCP and ketamine. 8,9 Hypertension and nystagmus, which were observed in our patient, are hallmarks of PCP intoxication, and both have been reported to occur in about 57% of the cases and to resolve within 4 h of PCP consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The most common physical effect is tachycardia (8). Additional studies have shown that, apart from tachycardia, tachypnea, hypertension, mydriasis, agitation, and cerebellar symptoms are also among common symptoms (9)(10)(11). Having observed that 30% of the physicians who participated in our study did not have any idea about this matter, physicians working in emergency services should be more knowledgeable about the common physical effects of these substances.…”
Section: Acil Servis Hekimlerinin Sentetik Kannabinoidler Hakkındaki mentioning
confidence: 75%
“…a dissociative state with detachment of body and mind, leading some users to experiment with imminent death experiences. [66,67] The effects sought also include euphoria, empathy, and a pleasant intensification of sensory experiences, in particular music. [68] Nevertheless, these effects are often accompanied by negative effects like visual hallucinations, trembling, confusion, agitation or somnolence and memory loss.…”
Section: Methoxetaminementioning
confidence: 99%
“…Users also regularly present signs of sympathomimetic toxicity, generally with elevated blood pressure and tachycardia. [59,67] Cerebellar toxicity with dysarthria can occur, accompanied by unsteady gait, nystagmus etc. [69] Medical care of acute MXE intoxication is based on symptomatic treatment with benzodiazepines in case of agitation and hypertonia, and with beta-blockers in case of sympathomimetic toxicity.…”
Section: Methoxetaminementioning
confidence: 99%
See 1 more Smart Citation